Barriers and Challenges to Waste Management Hindering the Circular Economy in Sub-Saharan Africa - Justice Kofi Debrah; Godfred Kwesi Teye; Maria Alzira Pimenta Dinis (Urban Science, 2022)
More and more, waste generated in most parts of the Western world has been recycled and transformed into new circularity products. However, managing waste within Sub-Saharan Africa (SSA), such as in Ghana, has become a challenge due to the continued practice of the old traditional linear waste economy, that is, the taking, making and disposing methods of management, representing a threat to global environmental sustainability. Despite the need to revise current linear waste management (WM) in order to turn to the circular economy (CE) model, which consists of the concept of renew, remake and share, to advance sustainable development, a number of factors restrict the CE realization in practice, specifically in developing countries. An integrative methodology was used in this article to identify some of the challenges that hinder the achievement of CE in SSA countries. The results revealed the absence of educational programs and public awareness of waste management activities. The findings also highlight the lack of political will, funding and national policies on WM as some of the most significant issues. The study contributes to further encouraging policymakers and policy implementers, entrepreneurs and relevant interested groups to commit resources to sustainable WM services aiming to advancing CE in SSA countries.